2004
DOI: 10.1016/j.orthres.2003.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Sequential dynamics of inflammatory cytokine, angiogenesis inducing factor and matrix degrading enzymes during spontaneous resorption of the Herniated disc

Abstract: Intervertebral disc herniation (HD) is one of the most common orthopaedic conditions. MRI analysis of H D has revealed a spontaneous resorption mechanism related with neo-vascularization. It appears that the interaction of activated macrophages with disc tissues leads to the generation of inflammatory cytokines. Moreover, inflammatory cytokines such as tumor necrosis factor-a (TNF-a) is required for the induction of angiogenesis inducing factors such as vascular endothelial growth factor (VEGF) or matrix degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 25 publications
1
71
1
5
Order By: Relevance
“…MMP production in ID tissue is mediated by cytokines, growth factors and inflammatory mediators. The role of interleukin-1 (IL-1) and tumor necrosis factor-a (TNF-a) has been documented in vitro [15]. Growth factors are known to affect the process of ID degeneration by inducing neovascularization and regulating MMP expression levels [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP production in ID tissue is mediated by cytokines, growth factors and inflammatory mediators. The role of interleukin-1 (IL-1) and tumor necrosis factor-a (TNF-a) has been documented in vitro [15]. Growth factors are known to affect the process of ID degeneration by inducing neovascularization and regulating MMP expression levels [23].…”
Section: Discussionmentioning
confidence: 99%
“…Contact between the herniated fragment of the ID and the epidural space was thought to trigger an autoimmune response with inflammatory cell infiltration and in situ neovascularization, leading to the progressive resorption of the herniated fragment and regression of symptoms. Mounting evidence has shown that growth factors, matrix metalloproteinases (MMPs) and inflammatory mediators, such as cytokines, play a key role in ID homeostasis and pathology [9,15]. However, the role of such molecules in the pathogenesis of ID herniation as well as in the spontaneous regression of herniated disc fragments remains only partially elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pathobiological changes and inflammatory cascades, such as the induction of programmed cell death (apoptosis), chemotactic recruitment of leukocytes and the activation of matrix-degrading metalloproteinases (MMPs) can be expected [4,27,51].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we can infer that increased VEGF expression may aggravate IVD degeneration through the progress of atherosclerosis or calcification leading to occlusion of endplate openings, and further exacerbate low back pain by inducing nociceptive nerve ingrowth into degenerated disc. Conversely, others suggest that the VEGF is protective against IVD degeneration via the neovascularization of the degenerative disc (Haro et al, 2002;Kato et al, 2004;Walsh, 2004). Angiogenesis may be regarded as a part of the repair response (Haro et al, 2002).…”
Section: Discussionmentioning
confidence: 99%